The influence of patient-centered communication on psychological distress: the chain mediating role of health-related self-efficacy and healthy lifestyle behaviors and the moderating role of social media use - Siying Angus Gong; Song Harris Ao; Yue Selene Chen (Frontiers in Psychiatry)
BackgroundPsychological distress remains a pervasive issue, influenced by complex psychosocial and behavioral mechanisms. Nevertheless, there is a paucity of research exploring how patient-centered communication influences psychological health through intermediary mechanisms, especially the sequential roles played by health-related self-efficacy and healthy lifestyles.MethodThis study was conducted on de-identified public data from the Health Information National Trends Survey 2022 (HINTS 6), with a sample size of 6,252. It first proposed and tested a chain mediation model linking patient-centered communication and psychological distress, mediated by health-related self-efficacy and healthy lifestyle behaviors. Based on the model, it explored the moderating role of social media use in this model.ResultThis study found that patient-centered communication is negatively associated with psychological distress and health-related self-efficacy and healthy lifestyle behavior play a chain mediating role between them. Moreover, social media use enhances the positive impact of patient-centered communication on health-related self-efficacy.ConclusionThis study demonstrates the generalizability of patient-centered communication in alleviating psychological distress through the chain mediating pathway of health-related self-efficacy and healthy lifestyle behaviors. Notably, it reveals the moderating effect thresholds of social media use on this pathway. These findings provide both theoretical foundations and practical guidelines for: (1) optimizing doctor-patient communication strategies; (2) media literacy interventions under the WHO health literacy framework; and (3) improving psychological support in post-pandemic telemedicine.